Acute effects of plyometric and resistance training on running economy in trained runners - Marcello, R. T.; Greer, B. K.; Greer, A. E. (The Journal of Strength and Conditioning Research, 2017)
Results regarding the acute effects of plyometrics and resistance training (PRT) on running economy (RE) are conflicting. Eight male collegiate distance runners (21 ± 1 years, 62.5 ± 7.8 ml/kg/min VO2 peak) completed VO2 peak and 1 repetition maximum (1RM) testing. Seven days later, subjects completed a 12 minutes RE test at 60 and 80% VO2 peak, followed by a PRT protocol or a rested condition of equal duration (CON). The PRT protocol consisted of 3 sets of 5 repetitions at 85% 1RM for barbell squats, Romanian deadlifts, and barbell lunges; the same volume was used for resisted lateral lunges, box jumps, and depth jumps. Subjects completed another RE test immediately after the treatments and 24 hours later. Subjects followed an identical protocol 6 days later with condition assignment reversed. Running economy was determined by both relative VO2 (ml/kg/min) and energy expenditure (EE) (kcal/min). There was a significant (p = 0.05) between-trial increase in VO2 (37.1 ± 4.2 ml/kg/min PRT vs. 35.5 ± 3.9 ml/kg/min CON) and EE (11.4 ± 1.3 kcal/min PRT vs. 11.0 ± 1.4 kcal/min CON) immediately after PRT at 60% VO2 peak, but no significant changes were observed at 80% VO2 peak. Respiratory exchange ratio was significantly (p = 0.05) reduced 24 hours after PRT (0.93 ± 0.0) as compared to the CON trial (0.96 ± 0.0) at 80% VO2 peak. Results indicate that high-intensity PRT may acutely impair RE in aerobically trained individuals at a moderate running intensity, but that the attenuation lasts less than 24 hours in duration.